Evaluating the risks of arrhythmia following electrical injury: Two cases of electrical injuries in the upper limbs. (May 2020) - Jingo, Koichi; Kondo, Yutaka; Hirano, Yohei; Inoue, Juri; Kawasaki, Takaaki; Miyoshi, Yukari; Ishihara, Tadashi; Okamoto, Ken; Tanaka, Hiroshi
Electrical injuries induce ventricular arrhythmias, which are lethal. Therefore, it is important to evaluate the risk of arrhythmias at initial presentation to the emergency department in cases of electrical injuries. Here, we report two cases with electrical injuries, where current flowed between the upper limbs, requiring 24-h hospitalization for arrhythmia monitoring. The patients were 57- and 30-year-old men, who sustained separate electrical injuries (6600 V, line voltage), with current flow from one hand to the other. They did not develop any ventricular arrhythmias during hospitalization and were discharged. The risk for ventricular arrhythmias is lower for electrical injuries occurring between the upper limbs than for those occurring between the upper and lower limbs. We conclude that 24-h hospitalization for monitoring of patients with electrical injuries of the upper limbs may be sufficient.